Getting Past the ‘Post-’: History and Time in the Fiction of David Mitchell - Maria Beville ([sic])
This paper examines David Mitchell’s Cloud Atlas (2004) and The Thousand Autumns of Jacob de Zoet (2010), with a particular focus on history and narrative time. It seeks to offer an alternative perspective on the multiple and intertwined fictional narratives of Mitchell’s oeuvre as these evidence a move past the "post-" of postmodernism. Keywords: David Mitchell, time, narrative, historiography, experimental fiction, post-postmodernismPostmodernism has cast an extended influence over much literary criticism in the last fifty years. However, with the end of the noughties now in reach of critical hindsight, and with the shock of September 11, 2001 beginning to subside, significant attention is turning once again toward the new literary vanguard. Efforts to discuss post-postmodernism, critical realism, new materialism, and new-millennial writing are certainly on a par with artistic and literary efforts to move beyond postmodernist playfulness and relativism. Within this broader framework, scholars have debated the fiction of David Mitchell, often straining to include his literary experimentalism with categories of the postmodern. However, resisting these efforts in the two novels chosen for analysis here, Mitchell’s writing appears to return from the abstraction and playfulness of postmodern poetics to settle as an engaged writing practice concerned with the materiality of time and of history. With time and history as its conceptual anchors, Mitchell’s more literary practice in the novels discussed here confronts developed postmodernist approaches to the past through an insistence upon a sense of time that abjures postmodern paradigms of uncertainty and relativity. This paper will examine time and narrative in relation to selected recent works by Mitchell in order to allow an alternative perspective on the workings of the multiple and intertwined fictional narratives across his novels; a perspective which can enlarge our understanding of how Mitchell continues to write his way out of the rhizome of postmodernist poetic practice.